How college students evaluate and share “fake news” stories - Leeder, Chris (Library & information science research, 2019)
The spread of “fake news” stories online has become a pressing concern in the United States and around the world in recent years. Social media platforms enable the rapid spread of such misinformation and also make evaluating the credibility of online information more difficult. Since college students are frequent users of social media, they are particularly likely to be exposed to fake news. A survey was conducted with 63 undergraduate students in which they identified and evaluated examples of both fake and real news stories and reported their associated information behaviors. Results showed correlations between accurate identification of fake news stories and specific critical evaluation behaviors and strategies. However, students were unable to accurately evaluate their own skills, and their willingness to share fake news stories on social media was not related to accurate identifications or evaluations of trustworthiness. This study contributes to the understanding of not just how accurately students evaluate fake news stories, but of the specific information-seeking behaviors and critical evaluation strategies that are associated with accurate identifications and evaluations and with willingness to share news stories on social media. Implications for educators and directions for future research are discussed. •College students were asked to identify fake and real news stories and answered a survey about their information behaviors.•Students correctly identified 64.29% of fake news and 60.58% of real news stories.•Higher-performing students demonstrated stronger critical evaluation behaviors and greater use of verification strategies.•Students were not able to accurately assess their level of skill in evaluating fake news stories.•Willingness to share news stories was unrelated to trustworthiness evaluations and accuracy of identifications.